Emotion regulation as a boundary condition of the relationship between team conflict and performance: A multi‐level examination. (26th September 2012) - Jiang, Jane Yan; Zhang, Xiao; Tjosvold, Dean
Summary: Although task conflict is widely believed to be beneficial whereas relationship conflict is destructive, evidence overall does not support this conclusion. This study develops the idea that the emotion regulation abilities of team members affect how they manage task and relationship conflict, both as individuals and as a team. Findings from a field study involving 39 teams support the argument that individuals skilled in emotion regulation can take advantage of task conflict to perform effectively and limit the negative impact of relationship conflict. Groups that have individuals highly skilled in emotion regulation were also found to make good use of team conflict. Results suggest that emotion regulation skills contribute to the effective management of task conflict and relationship conflict at both individual and group levels. Copyright © 2012 John Wiley & Sons, Ltd.